(3GdefGaSI hGdJQhjL GdJWHjbjs (3BdjGJ GdTQcGJ dJMSjf GdeQGcR GdJfGaSjIs - (3GdfLGQ(B, (3aQjOs ((3GdEScfOQjIs (3eDSSI THGH GdLGeYIs, 2006)
(3JMdjd ehba GdefGaSI hGdJfGaSjI(B- (3JMdjd GdaQU GdJShjbjI(B- (3GdegGQGJ GdESJQGJjLjI(B- (3GdJQhjM hGdGJUGdGJ GdJShjbjI(B- (3GSJQGJjLjGJ GdYdGbGJ GdYGeI hGdJQhjL(B- (3HMhK GdYdGbGJ GdYGeI hbjGS GdBQGA(B- (3CSGdjH GdJMdjd GdJfGaSj hGdCReGJ(B- (3eONd GdebGQGfGJ GdJWhQjI GdeSJeQI dJMSjf GdeQGcR GdJfGaSjIs
Keywords: (3GdJQhjLs; (3GdefGaSIs